'My mother was a kitchen girl': legal and policy responses to the problem of care for women who provide care in South Africa. Issue 1 (4th May 2022) - Fapohunda, Adenike
ABSTRACT: Domestic labour or care work creates the conditions through which other labour can occur, however, the value that this work provides is scarcely recognised when lawmakers consider its remuneration and regulation. This paper investigates legal discrimination against providers of domestic labour in South Africa, especially at home involving women in relationships and domestic workers. This is done by considering how labour law and gender equity law as well as the Constitution produce inequitable outcomes for women providing care services and contrasting the realities of care workers with legal protections. It also considers the ways in which the COVID-19 pandemic has changed the reality of care. Lastly, it outlines the ways in which the law can enable more equitable dispensations of labour.